The Archive of the Sin Temple in Khafajah (Tutub) - Harris, Rivkah
1. Excavations in the Diyala Region — 2. Extant Text Material from the Diyala Region — 3. The Archive. — 4. The Formulae of the Loan Contracts — 5. Economic Background of the Archive — 6. Historical Background of the Archive — 7. King List and Synopsis of the History of Tutub.